Characterisation of III‐nitride materials by synchrotron X‐ray microdiffraction reciprocal space mapping. Issue 3 (21st December 2012) - Kachkanov, Vyacheslav; Dolbnya, Igor; O'Donnell, Kevin; Lorenz, Katharina; Pereira, Sergio; Watson, Ian; Sadler, Thomas; Li, Haoning; Zubialevich, Vitaly; Parbrook, Peter; Toropov, Alexey; Ivanov, Sergey
Abstract X‐ray Reciprocal Space Mapping (RSM) is a powerful tool to explore the structure of semiconductor materials. However, conventional lab‐based RSMs are usually measured in two dimensions (2D) ignoring the third dimension of diffraction‐space volume. We report the use of a combination of X‐ray microfocusing and state‐of‐the‐art 2D area detectors to study the full volume of diffraction–space while probing III‐nitride materials on the microscale. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)